'Superimposed miracles': an extremely rare case of a septuagenarian with an unrepaired tetralogy of Fallot: a case report. Issue 12 (30th November 2021) - Suzuki, Makiko; Matsumoto, Kensuke; Izawa, Yu; Hirata, Ken-Ichi
Abstract: Background: Although the life expectancy of patients with tetralogy of Fallot (TOF) is comparable to that of the general population due to advancements in surgical intervention, if untreated, patients with TOF may die during their childhood. However, it has been anecdotally reported that a small number of patients with unrepaired TOF survived into their senescence. Case summary: A 71-year-old man with a history of multiple heart failure admissions was referred to our institute after successful cardiopulmonary arrest resuscitation. Transthoracic echocardiography showed the overriding of the aorta on a large ventricular septal defect and right ventricular hypertrophy, along with severe pulmonary stenosis (PS), all of which indicated unrepaired TOF. Computed tomography revealed a patent Blalock–Taussig shunt, which was constructed at the age of 19 years. Coronary angiography revealed multivessel coronary stenoses. Although radical intracardiac repair was not performed due to his multiple comorbidities, his heart failure symptoms were significantly improved owing to proper medication titration. One year following discharge, the patient was well and enjoyed playing golf. Discussion: Specific anatomical, functional, and haemodynamic characteristics may be required for the long-term survival of patients with TOF. Pulmonary stenosis should be initially mild to guarantee pulmonary flow during childhood and adolescence, and gradual PS exacerbation should be paralleled with systemic-to-pulmonary collateral development or an extracardiac shunt. Moreover, reduced left ventricular compliance may act as a balancing factor against a right-to-left shunt. The presence of all of these special requirements may have contributed to the unusual survival for this patient.